(untitled) - King, David C. (New Jersey, 2003)
Explore the American West with the people who settled it! In 1805, when William Clark first spotted the Pacific Ocean-highlighting the famous Lewis and Clark expedition across the continent-it marked the beginning of a massive westward movement that lasted through the century. Westward Expansion provides a rare glimpse into the day-to-day experiences of pioneering Americans as they followed Lewis and Clark's lead, risking their lives to explore, farm, seek their fortunes, and establish communities in what had been considered a vast wilderness. Through rich primary sources, you'll find yourself living and working alongside the brave men and women who came to typify the American West, including pioneers from the eastern states, from Europe, and from Asia; Native Americans defending their homeland; freed slaves searching to carve their own destinies out of America's wilderness; prospectors searching for gold and silver; and many other colorful characters. From Daniel Boone's account of first exploring Old Kentucky to Chief Joseph's explanation of why he would no longer fight against the U. S. Army, Westward Expansion presents a wealth of period documents, including diaries, letters, articles, advertisements, speeches, and more, from both famous figures and ordinary citizens. Find out how all of these American voices working together helped make this country what it is today.
Keywords: West (U.S.),West (U.S.),Frontier and pioneer life,Phía Tây nước Mỹ; History,Discovery and exploration,Lịch sử; West (U.S.)